2018
DOI: 10.1002/hbm.24039
|View full text |Cite
|
Sign up to set email alerts
|

Presurgical language fMRI: Clinical practices and patient outcomes in epilepsy surgical planning

Abstract: The goal of this study was to document current clinical practice and report patient outcomes in presurgical language functional MRI (fMRI) for epilepsy surgery. Epilepsy surgical programs worldwide were surveyed as to the utility, implementation, and efficacy of language fMRI in the clinic; 82 programs responded. Respondents were predominantly from the US (61%) academic programs (85%), and evaluated adults (44%), adults and children (40%), or children only (16%). Nearly all (96%) reported using language fMRI. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 28 publications
4
48
0
Order By: Relevance
“…Based on these results, the authors recommended routine follow-up for patients with atypical language fMRI with a Wada test. Other authors have voiced similar concerns and recommended routinely repeating language fMRIs that indicate right dominance (Benjamin et al, 2018). Therefore, the present work is useful in showing that fMRI can identify right-lateralized cases with high confidence.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Based on these results, the authors recommended routine follow-up for patients with atypical language fMRI with a Wada test. Other authors have voiced similar concerns and recommended routinely repeating language fMRIs that indicate right dominance (Benjamin et al, 2018). Therefore, the present work is useful in showing that fMRI can identify right-lateralized cases with high confidence.…”
Section: Discussionmentioning
confidence: 70%
“…While the advantages of different implementations of the laterality index are under debate (Wilke and Lidzba, 2007;Bradshaw et al, 2017a), they have proven to be robust, provided that the data are of sufficient quality (Wegrzyn et al, 2019). With fMRI being able to predict the results of the Wada test with accuracies around 90% (Dym et al, 2011;Bauer et al, 2014) it has become an established tool for lateralizing language (Binder, 2011;Szaflarski et al, 2017;Benjamin et al, 2018). Its non-invasive nature is an important asset for a biomarker, as it can be easily repeated, extended and used on many patients, as well as healthy normative samples (Gabrieli et al, 2015;Dubois and Adolphs, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A second survey, focused on clinicians' interpretation of fMRI and patient outcomes, was also forwarded to the "epilepsy surgical program [director], or a senior clinician involved in determining patients' surgical eligibility" with this survey. While these surveys were intended to be paired, most sites did not submit paired responses, and thus the clinical survey is reported separately [Benjamin et al, 2018]. Nine respondents from that manuscript completed both surveys; their responses on accuracy and outcomes are also included here (Section 3.6).…”
Section: Surveymentioning
confidence: 99%
“…The optimal choices for each variable continue to be subject to debate, though they clearly alter the precise language map obtained [e.g., Benjamin et al, 2018 Figure 3]. While this variation may be less likely to impact lateralization, it will certainly impact localization; and we recently reported that 44% of epilepsy surgical programs use fMRI for this purpose [Benjamin et al, 2018].…”
Section: Introductionmentioning
confidence: 96%